Pembelajaran Perspektif Al-Zarnuji: Relevansi Nilai-Nilai Pendidikan Islam sebagai Strategi Efektif di Era Kontemporer - Mariati, Mariati; Walidin, Warul (Tadabbur: Jurnal Peradaban Islam, 2025)
This article explores the principles of Islamic education developed by Imam Al-Zarnuji in his book Ta‘lim al-Muta‘allim, as well as their relevance to modern educational practices. Using a literature review method with a qualitative approach, this study analyzes key principles such as sincerity of intention in seeking knowledge, respect for teachers, the importance of patience, applying knowledge, choosing beneficial knowledge, and the emphasis on manners and discipline in learning. Al-Zarnuji also outlines the characteristics of an ideal teacher, which include being knowledgeable (ʿālim), pious (wara’), authoritative, patient, and compassionate. The findings show that the educational principles in Ta‘lim al-Muta‘allim remain relevant in shaping holistic, value-oriented learning and in supporting the development of student character amid global challenges and the digital era. Al-Zarnuji’s educational values have the potential to serve as a strong ethical and philosophical framework for designing meaningful, civilized, and character-oriented educational systems.